Effect of Work Movements, Job Promotion, and Compensation towards Employee Performance - Mai Yuliza; Mezi Desri; Nasfi Nasfi (Jurnal Akuntansi, Manajemen dan Ekonomi, 2021)
The role of human resources has a critical and strategic position in the organization to achieve goals. Human resources are essential for companies in managing and utilizing employees to function productively to achieve company goals. This study's objectives are to analyze and provide empirical evidence on the effect of work movements, job promotion, and compensation on employee performance at the Ibnu Sina Simpang Empat Islamic Hospital. The type of research used in this research is quantitative research. This study's population was all Islamic Hospital Ibnu Sina Simpang Empat, totaling 239 employees, and the final sample counted as many as 150 employees. The data analysis technique used multiple linear regression analysis. This research aims to analyze and provide empirical evidence on work movements, job promotion, and compensation on employee performance at the Ibnu Sina Simpang Empat Islamic Hospital, Pasaman Barat, Sumatera Barat with yields as follows: (1) Work Movements is not affect employee performance significantly. (2) Job Promotion is affecting employee performance significantly. (3) Compensation is affecting employee performance significantly. (4) Work Movements, Job Promotion, and Compensation is affecting employee performance simultaneously. Work Movements, Job Promotion, and Compensation to employee performance variables have contributed a level of strength, i.e., 52,6 percent.